Heavy metal resistance in bacteria from animals. (February 2019) - Argudín, M.A.; Hoefer, A.; Butaye, P.
Abstract: Resistance to metals and antimicrobials is a natural phenomenon that existed long before humans started to use these products for veterinary and human medicine. Bacteria carry diverse metal resistance genes, often harboured alongside antimicrobial resistance genes on plasmids or other mobile genetic elements. In this review we summarize the current knowledge about metal resistance genes in bacteria and we discuss their current use in the animal husbandry. Highlights: Metal resistance genes are widely distributed in bacteria. Diverse systems for co-selection of metal and antimicrobial resistance genes exist. Prudent use of metals in animal feed is needed to avoid co-selection.